Quality Assurance-Student Involvement Confluence: Exploring Gaps and Implications for Higher Education Institutions in Zimbabwe - Ncube, M. (South African Journal of Higher Education, 2020)
Since postulation, the student involvement (SI) theory of development by Alexander Astin has been crucial in reconfiguring and maximizing the higher education experience through improving the quality. Student-input is instrumental in examining student-experience and managing the quality in higher-education-institutions (HEIs). Amidst industrial revolutionary technologies that transcend bureaucratic procedures governing HEIs, involving students, most of whom are technologically savvy, potentially sparks innovation. Transitioning from education 3.0 to doctrine education 5.0 has implications of quality assurance (QA)-student involvement (SI) confluence on Zimbabwe’s HEIs. Two out of nine HEIs in Matabeleland were selected for convenience of location. Findings show SI should precede QA outcomes although HEI practices do-not reflect this important means-to-an-end-relationship. To attain quality under the doctrine, SI must satisfy students on all doctrine 5.0’s standards. Few HEI-programmes target SI for QA. Programming gaps affect student-learning, hence innovative learning-systems must respond to evolving societal-needs and satisfy students-diversity including in curriculum-development; staff-quality; and research and development-projects. Thus, SI reflects placation at best and tokenism at worst. Government/HEIs must export leading academics, fund their attainment of updated skills-set from modernised countries, and deploy them to reorient HEI programmes while concurrently modernising industries to ensure newly attained skills have platforms for applicability.